2017
DOI: 10.1186/s13756-016-0162-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial etiology of bloodstream infections and antimicrobial resistance in Dhaka, Bangladesh, 2005–2014

Abstract: BackgroundBloodstream infections due to bacterial pathogens are a major cause of morbidity and mortality in Bangladesh and other developing countries. In these countries, most patients are treated empirically based on their clinical symptoms. Therefore, up to date etiological data for major pathogens causing bloodstream infections may play a positive role in better healthcare management. The aim of this study was to identify the bacterial pathogens causing major bloodstream infections in Dhaka, Bangladesh and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
36
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 43 publications
(41 reference statements)
12
36
3
Order By: Relevance
“…Viridians streptococci was 100% sensitive to penicillin, but two other studies have reported that penicillin resistance rates have increased to more than 50% [38, 39]. The penicillin resistance rate of Streptococcus pneumoniae was 30%, similar to many European countries (20% to 50%), although much higher rates were reported in other Asian countries [40, 41], while there were only a few countries with lower rates (less than 10%) [9, 32, 42]. Therefore, the penicillin aslo resulted as a treatment choice for Streptococcus spp.…”
Section: Discussionmentioning
confidence: 95%
“…Viridians streptococci was 100% sensitive to penicillin, but two other studies have reported that penicillin resistance rates have increased to more than 50% [38, 39]. The penicillin resistance rate of Streptococcus pneumoniae was 30%, similar to many European countries (20% to 50%), although much higher rates were reported in other Asian countries [40, 41], while there were only a few countries with lower rates (less than 10%) [9, 32, 42]. Therefore, the penicillin aslo resulted as a treatment choice for Streptococcus spp.…”
Section: Discussionmentioning
confidence: 95%
“…Publication year 2004-2010 11 (23.9) (Arifeen et al, 2009;Brooks et al, 2005;Haque and Salam, 2010;Khan et al, 2004;Mahbubur et al, 2007;Monjur et al, 2010;Nahar et al, 2004;Rahman et al, 2005;Saha et al, 2009;Shahriar et al, 2010;Shill et al, 2010Shill et al, ) 2011Shill et al, -2014 14 (30.4) (Afroz et al, 2014;Ahmed et al, 2011Ahmed et al, , 2014Akram et al, 2014;Akter et al, 2014;Begum et al, 2013;Chiou et al, 2014;Dutta et al, 2013;Haque et al, 2011;Hossain et al, 2014;Islam et al, 2014;Khan et al, 2013;Rahman et al, 2014;Ud-Din et al, 2013-2018 21 (45.7) (Aftab et al, 2016;Ahmed et al, 2017Ahmed et al, , 2018Ahsan et al, 2016;Akter et al, 2016Akter et al, , 2017Begum et al, 2016;Chakraborty et al, 2016;Chowdhury and Parial, 2015;Haque et al, 2015;Hasan et al, 2016;Islam and Shamsuzzaman, 2015;Jobayer et al, 2017;Khanam et al, 2015;Nazme et al, 2017;…”
Section: Characteristicsmentioning
confidence: 99%
“…Community-acquired 5 (10.9) (Akter et al, 2014;Arifeen et al, 2009;Brooks et al, 2005;Mahbubur et al, 2007; (Aftab et al, 2016;Chiou et al, 2014;Hasan et al, 2016;Islam and Shamsuzzaman, 2015;Nahar et al, 2004;Rahman et al, 2014;Suchi et al, 2017) E-test 5 (10.9) (Arifeen et al, 2009;Begum et al, 2016;Khan et al, 2013;Mahbubur et al, 2007;Saha et al, 2009) Did not mention 5 (10.9) (Ahmed et al, 2018;Akram et al, 2014;Islam et al, 2014;Nazme et al, 2017;Shill et al, (Akter et al, 2016;Chowdhury and Parial, 2015;Haque et al, 2015;Khan et al, 2013;Nazme et al, 2017;Rahman et al, 2014;Saha et al, 2015;Shill et al, 2010;Suchi et al, 2017;Yasmeen et al, 2015) Bloodstream infection 7 (15.2) (Afroz et al, 2014;Ahmed et al, 2017Ahmed et al, , 2018Ahsan et al, 2016;Brooks et al, 2005;Khanam et al, 2015;Monjur et al, 2010) Gastroenteritis 8 (17.4) (Ahmed et al, 2011(Ahmed et al, , 2014Akter et al, 2017;Begum et al, 2016;Khan et al, 2004;…”
Section: Source Of Infectionmentioning
confidence: 99%
“…This study found a higher prevalence of Gram-positive bacteria (GPB), con rming previous studies [Zhu et al, 2018, Rui et al 2019. It is valid to say that, as mentioned, this prevalence may vary according to region, and therefore, some studies report a higher prevalence of Gram-negative bacilli (GNB) [Ahmed et al, 2017, Toyofuku et al, 2019. This variation can be explained by several factors, such as an increase in the practice of invasive procedures, prophylactic treatment with antimicrobials that have high activity against GNB and have little or no activity against GPB, greater recognition of CoNS as pathogens, immunological status of the patient, arti cial climate of the hospital, hand hygiene of health professionals, and hospital service pro le.…”
Section: Discussionmentioning
confidence: 99%